Structure evolution of aluminosilicate sol and its structure‐directing effect on the synthesis of NaY zeolite. Issue 1 (31st January 2017) - Zhao, Xiaomeng; Liu, Rugeng; Zhang, Heng; Shang, Yunshan; Song, Yu; Liu, Chao; Wang, Tao; Gong, Yanjun; Li, Zhihong
Abstract : This work sheds some light on the impact of the SiO2 /Al2 O3 ratios of aluminosilicate sols on structure evolution, including particle size, fractal dimension, and the interplay between the fractal dimension and the activity to generate NaY zeolite. The mechanisms regulating the growth behaviour of the sols during ageing are proposed. Abstract : Understanding the growth behaviour of an aluminosilicate sol during ageing is necessary for the design of the sol and the synthesis of NaY zeolite. Herein, aluminosilicate sols with three different SiO2 /Al2 O3 ratios were prepared and aged for varying times at 293 K. The sol was then introduced as a structure‐directing agent in the feedstock gel to generate NaY zeolite. The structure evolution of the sol species during the ageing process was studied by in situ small‐angle X‐ray scattering (SAXS) using synchrotron radiation. SAXS data, in combination with transmission electron microscopy images, Raman spectra and X‐ray diffraction patterns, present a detailed description of the sol species, revealing an interplay between the fractal structure and reactivity to generate NaY zeolite. The SiO2 /Al2 O3 ratios in the sol play a critical role in the structure evolution of the aluminosilicate species during the ageing, particularly with respect to their size distributions and the fractal dimensions. The species with suitable size and compactness in the sol are found to be an active precursor for achieving a highly crystalline NaY zeolite. The sol with an SiO2 /Al2 O3 ratio of 20 possesses active species with a mass fractal dimension D m of 2.0–2.6 after ageing, which leads to the formation of a well crystallized NaY zeolite. However, the high‐silica sol‐25, with an SiO2 /Al2 O3 ratio of 25, and alumina rich sol‐10, with a ratio of 10, experience growth at either slow or fast rates. In these cases the active species have smaller D m (1.1–1.9) or larger D m (2.6–2.8), respectively, displaying low/poor activity to generate NaY zeolite. The mechanisms regulating the growth behaviour of the sols during ageing are proposed.